Urban risk factors for human Rift Valley fever virus exposure in Kenya - Keli Nicole Gerken; Francis Maluki Mutuku; Bryson Alberto Ndenga; Gladys Adhiambo Agola; Eleonora Migliore; Eduardo Palacios Fabre; Said Malumbo; Karren Nyumbile Shaita; Izabela Mauricio Rezende; A. Desiree LaBeaud (Public Library of Science (PLoS), 2022)
The Rift Valley fever virus (RVFV) is a zoonotic arbovirus that can also transmit directly to humans from livestock. Previous studies have shown consumption of sick animal products are risk factors for RVFV infection, but it is difficult to disentangle those risk factors from other livestock rearing activities. Urban areas have an increased demand for animal source foods, different vector distributions, and various arboviruses are understood to establish localized urban transmission cycles. Thus far, RVFV is an unevaluated public health risk in urban areas within endemic regions. We tested participants in our ongoing urban cohort study on dengue (DENV) and chikungunya (CHIKV) virus for RVFV exposure and found 1.6% (57/3,560) of individuals in two urban areas of Kenya had anti-RVFV IgG antibodies. 88% (50/57) of RVFV exposed participants also had antibodies to DENV, CHIKV, or both. Although livestock ownership was very low in urban study sites, RVFV exposure was overall significantly associated with seeing goats around the homestead (OR = 2.34 (CI 95%: 1.18-4.69, p = 0.02) and in Kisumu, RVFV exposure was associated with consumption of raw milk (OR = 6.28 (CI 95%: 0.94-25.21, p = 0.02). In addition, lack of piped water and use of small jugs (15-20 liters) for water was associated with a higher risk of RVFV exposure (OR = 5.36 (CI 95%: 1.23-16.44, p = 0.01) and this may contribute to interepidemic vector-borne maintenance of RVFV. We also investigated perception towards human vaccination for RVFV and identified high acceptance (91% (97/105) at our study sites. This study provides baseline evidence to guide future studies investigating the urban potential of RVFV and highlights the unexplored role of animal products in continued spread of RVFV.